Call the midwife. Season thirteen [videorecording (DVD)] - Thomas, Heidi, 1962- (BBC Studios, 2024)
The midwives of Nonnatus House continue to face complex medical and personal dilemmas as the multi-award-winning drama returns for a thirteenth series. It's 1969 and more babies than ever are being born in hospital. Pressure on maternity beds remains extremely high across the country. However, Poplar is coping better than most due to the popularity of home births under the auspices of the sisters. And a new midwife-training scheme sees Nonnatus House welcome a host of new midwives. The recruits face social problems arising from the docks, concerns among the Nigerian and Sylheti communities and health challenges from Cerebral Palsy, Tetanus and TB.